CONTEXTUAL ARCHITECTURE AS DEVELOPMENT STRATEGY IN THE EXTREME LAND FOR A MASTERPLAN DESIGN OF THE COMPLEX OF MATER DEI NUSANTARA HIGH SCHOOL BALIKPAPAN - Kusliansjah, Yohanes Karyadi; Suriansyah, Yasmin; Fauzy, Bachtiar; Patriajaya, Anneke Clauvinia (Universitas Telkom, 2024)
The development of the Nusantara Capital City (Ibu Kota Nusantara- IKN) triggers the needs indeveloping Mater Dei Nusantara Senior High School (SMA) complex as a supporting facility. Strategicallylocated in KM 10 Balikpapan, between Penajam Paser Utara and Samarinda, the school site has an extremephysical context of a steep hills, clay shale layers, a hot tropical climate and strong cultural values. Thedevelopment of this high school area faces problems and spatial physical environmental impacts that requiretechnical solutions in the preparation of a comprehensive contextual architectural-based masterplan. Thisstudy aims to generate contextual design guidance in developing the Mater Dei Nusantara High School masterplan through a descriptive-interpretative approach by observation, document review, problemsanalysis to the contextualised design solution generation. The result of the study is a masterplan of Mater Dei High School complex that applies the concept of green architecture that is contextual to the extremeenvironment and adapts the form of local architecture of West Kutai Lamin. This study is expected tobebeneficial in the development strategy of similar extreme environments in East Kalimantan, Indonesia. Keywords : Balikpapan, Contextual architecture, Development strategy in the extreme land, Masterplanof the school complex.